Sensor network integration for a medical device using CDG - Delgado-Gomes, Vasco (2020)
The weakness of the deep layer of lumbar or cervical spine muscles (so-called multifidus muscles) is among the most common causes for backpain. Frequent testing and measurements over a 20 years period of time showed a common weakness of this particular muscle group in more than 70% of investigated persons. Following a routine training has demonstrated an effective improvement in low back health. The Smart4Health project aims at empowering EU Citizens with an interoperable and exchangeable European Electronic Health Record (EHR) that will allow EU citizens to be active participants in managing their own health. As part of project activities, Smart4Health will upgrade existing physiotherapy devices with real-Time measurements and connectivity capabilities, meeting new medical device regulations. Force and angle sensors measurement technology will be connected and integrated in the Smart4Health framework, enabling the patient with a real-Time performance visualization and the treatment data upload for a secure cloud. The clinicians can then keep track of the patient treatment and made the necessary adjustments (if needed). The physiotherapy device and its sensors are connected over a secure network, enabling the data collection of health-related data. Moreover, an intelligent sensors network collecting citizen health and wellbeing data, adds information to citizen's EHR.